Intra- and inter-observer reliability of a new standardized diagnostic method using SPECT/CT in patients with osteochondral lesions of the ankle joint. Issue 1 (December 2016) - Hassink, Geneviève; Testa, Enrique; Leumann, André; Hügle, Thomas; Rasch, Helmut; Hirschmann, Michael
Abstract Background Single Photon Emission Computed Tomography-Computed Tomography (SPECT/CT) gains an important part of diagnostics in patients with osteochondral lesions (OCL). SPECT/CT is a hybrid imaging modality, which combines a 3D scintigraphy (SPECT) and computerized tomography (CT) into one single procedure and combines metabolic data, structural and mechanical information. The purpose of the study was to develop and evaluate a standardized method to anatomically localize and quantitatively analyze the bone SPECT tracer activity of the ankle joint using SPECT/CT. Methods OCL on the talus were diagnosed in 16 patients by 99mTc-HDP-SPECT/CT and MRI by specialized orthopedic surgeons and radiologists and retrospectively included. The articular superior surface of the talus was subdivided in six anatomical regions (T1–T6). Using customized software, absolute bone SPECT values for each anatomical area were analyzed. Relative bone tracer uptake was calculated in relation to specific reference regions representing bone SPECT tracer background activity. All measurements were performed twice by two independent observers, blinded to clinical information. Intraclass correlation coefficients (ICC) were calculated for inter- and intra-observer reliability. The intraclass correlation coefficients (ICC) showed an excellent inter- and intra-observer reliability. Results The intraclass correlation coefficients (ICC) of all six regions are between 1.00 and 0.84 which is defined as very good. Results from region T1 to T6 impair slightly due to measurement regime. All ICCs of observer 1 were nearly the same as the results of observer 2 in all regions. Conclusion The presented standardized SPECT/CT algorithm is clinically feasible and showed high inter- and intra-observer reliability. It might help to better understand the complex pathology of OCL on the talar dome. The major potential benefit of SPECT/CT is the assessment of the subchondral bone plate and the subchondral bone.